Strategi Pengembangan Pasar Keramik Belawan Sebagai Daya Tarik Wisata Belanja di Kota Medan - Femmy Indriany Dalimunthe; Anwari Masatip; L. Liyushiana; Dina Rosari (Tourism Scientific Journal, 2020)
This study aims to identify the strategic assumptions of Belawan Ceramics Market with a descriptive method approach. By compiling results from the perspective of customers and traders, this study analyzes strategic assumptions with the SWOT analysis tool. The results showed that consumers who came were consumers who had repeatedly visited the Ceramic Market, but the loyalty of visitors decreased for the fourth visit. Tourist considerations for visiting the Belawan Ceramics Market are diverse types of merchandise, traditional bargaining systems, interactions with direct traders, as well as structuring shopping space that is not rigid with social accessibility in the form of local community acceptance (especially traders) towards foreigners. From the SWOT analysis conducted, it was found that the strategies that could be carried out to develop the Belawan ceramics market were: opening stores early, adding collections of unique items, expanding promotions through social media, pentahelix synergy for more effective development, price competition considerations in accordance with the quality of the goods being marketed, complementing supporting tourism utilities such as lighting facilities and increasing the role of government and community self-help to increase the sense of security for visitors / tourists.